Invited review: Udder cleft dermatitis in dairy cows - A.-S. Vermeersch; R. Ducatelle; P. Geldhof; G. Opsomer (Journal of Dairy Science)
ABSTRACT: Udder cleft dermatitis (UCD) is a common dermatological condition of the udder skin in dairy cows. It is generally considered to be a multifactorial disease, being described in a rather limited amount of literature. Its cow and within-herd prevalence widely ranges between studies depending on the study characteristics, environment and breed. Known risk factors include husbandry practices and environmental factors, such as freestall housing, the use of mattresses as cubicle bases, and footbathing. Cow-related elements, such as udder conformation, parity, and lactation parameters are well-known risk factors for developing UCD. Despite being associated with a high incidence of veterinary-treated clinical mastitis and culling due to udder disease, the SCC of the milk is not influenced by UCD. Severe UCD lesions are characterized by chronic and persistent, dysregulated inflammation accompanied by hampered skin healing and an impaired skin barrier. There is a decrease in microbial diversity followed by dysbiosis and a concomitant overgrowth of opportunistic bacteria negatively affecting beneficial commensal bacteria. Concurrently, a shift in virulence factors most likely contributes to the creation of an environment favorable to pathogens. Anecdotally, mange mites have been associated with UCD but current literature refutes this. The role of treponemes remains inconclusive. Multiomics analysis of both transcriptomic and metagenomic severe UCD datasets, revealed the negative interaction of the facultative pathogen Streptococcus pyogenes with microbiome-associated virulence factors and the patient's transcriptome. No efficient curative treatments nor prevention strategies have been identified so far, although alginogel products have been described to have a positive effect on the healing process of severe lesions. All in all, UCD is a painful skin disease for which an array of miscellaneous risk factors have been identified. For the first time we assimilate literature on prevalence and risk factors, and results from recent elementary studies that provide insights into the pathogenesis of this challenging disease.